ANALISIS KESULITAN BELAJAR PESERTA DIDIK PADA MATERI PECAHAN CAMPURAN DALAM MENINGKATKAN MINAT BELAJAR - Lahacila, Nurfania; Anwar, Herson; Rizkyani Akolo, Ingka (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Mathematics plays an important role in daily life and the cognitive development of students. However, many students face difficulties in learning mathematics, particularly with complex topics like mixed fractions. These difficulties are often caused by internal factors, such as negative attitudes and low interest in mathematics, as well as external factors, such as the lack of effective learning media and family support. This study aims to analyze the learning difficulties of 4th-grade students at SDN 2 Tolangohula on the topic of mixed fractions and its impact on their interest in learning. A qualitative descriptive approach with a case study was used. The results show that internal factors such as negative attitudes and low motivation are major contributors to the students' difficulties, while external factors related to media use and family support also play a role. Efforts to create a pleasant learning environment and the use of nature-based learning media are expected to improve students' understanding and interest in mathematics